SIMULASI DUDUKAN LOADING-UNLOADING PANSER MORTIR MENGGUNAKAN SOFTWARE SOLIDWORKS - Izza, Rohul; Nuramal, Agus; F. Alqap, A. Sofwan (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2025)
The loading-unloading stand is part of the Panzer mortar loading-unloading tool which functions to hold the mortar and move the mortar from a vertical position to a horizontal position. In this test, the aim was to design a panzer mortar loading-unloading stand using Solidworks software, to find out how to simulate a loading-unloading stand and to determine the strength of the load on the panzer mortar loading-unloading stand. The simulation process on the loading-unloading stand was carried out to determine the von Mises stress, displacement and strain. von Mises stress and strain testing obtained a maximum result of 3,516 MPa and 5,744%  at the end of the shaft, displacement testing obtained a maximum result of 7,726 mm at the center of the shaft. The minimum factor of safety for loading- unloading stands is around 25.5 This occurs due to changes in the shape of the object being applied.